2018
DOI: 10.1007/s11307-018-1298-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Non-invasive Assessment of Hypoxia and Neovascularization with Magnetic Resonance Imaging in Benign and Malignant Breast Tumors: Initial Results

Abstract: Purpose: To develop a novel magnetic resonance imaging (MRI) approach for the noninvasive assessment of hypoxia and neovascularization in breast tumors. Procedures: In this IRB-approved prospective study, 20 patients with suspicious breast lesions (BI-RADS 4/5) underwent multiparametric breast MRI including quantitative BOLD (qBOLD) and vascular architecture mapping (VAM). Custom-made in-house MatLab software was used for qBOLD and VAM data postprocessing and calculation of quantitative MRI biomarker maps of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 56 publications
0
19
0
1
Order By: Relevance
“…Recently, we developed a non-invasive synergistic assessment of TME hypoxia and induced neovascularization in breast tumors; our initial results showed that this approach is promising to improve tumor characterization and provide insight into the distinct intratumoral heterogeneity of breast tumors [15]. In this study, we investigated the same algorithm for the differentiation of less aggressive luminal and more aggressive non-luminal breast cancers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we developed a non-invasive synergistic assessment of TME hypoxia and induced neovascularization in breast tumors; our initial results showed that this approach is promising to improve tumor characterization and provide insight into the distinct intratumoral heterogeneity of breast tumors [15]. In this study, we investigated the same algorithm for the differentiation of less aggressive luminal and more aggressive non-luminal breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The median age of this population was 57 years (range: 34-90 years). Some patients have been previously analyzed and reported in our pilot study [15].…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ob Letzteres (4) anhand mammographischen Bildmaterials möglich ist, bleibt fraglich. Hierfür liefern Modalitäten wie die Magnetresonanz und oder Positronen-Emissions-Tomographie [1,24] oder der multiparametrische Ultraschall [8] CAD-Systeme sind Parascript AccuDetect und VuCOMP M-Vu CAD. Eingangs bestanden neuronale Netzwerke (NNs) noch aus weitaus weniger verborgenen Schichten ("hidden layers") als heutzutage (ursprünglich bis zu 3, während heute durchaus 20 verborgene Schichten üblich sind; [7,9]…”
Section: Künstliche Intelligenz In Der Mammographieunclassified